The use of PCR and environmental swabs to identify mouse parvovirus post decontamination (Journal of Laboratory Animal Science, 2024)
Due to a history of recurrences of Mouse Parvovirus (MPV) outbreaks, a novel procedural solution to environmentally  screen previously contaminated rooms was explored. The authors wanted to evaluate a rapid, reliable means to test  the environment without using animals by investigating the use of environmental swabs to detect residual MPV after  rooms were depopulated and decontaminated. Polymerase Chain Reaction (PCR) was performed on environmental  swabs to determine the presence of DNA that could be indicative of residual MPV in the affected rooms. The absence  of MPV DNA demonstrated that the rooms were adequately decontaminated, and the likelihood of a re-infection  was minimal after repopulation. The use of PCR to confirm the absence of environmental MPV has been an excellent  method to determine the effectiveness of post outbreak decontamination.
Keywords: Mouse Parvovirus (MPV); Polymerase Chain Reaction (PCR); Environment; Decontamination; Replacement